Aloe vera cookies preparation, nutritional aspects, DPPH assay and physicochemical assay - Zahra, N; Saeed, MK; Nawaz, S; Gulzar, E (Bangladesh Journal of Scientific and Industrial Research, 2022)
Aloe vera has been widely used for various therapeutic purposes over the millennia. It is becoming increasingly popular due to its antiviral and antibacterial qualities. For many years, aloe vera has been employed in biomedical research. It's a fantastic way to boost the nutritional value of any food product. This research aims to expand on the nutritional value of cookies by including Aloe vera gel. It would focus on the substance's biological and pharmacological characteristics. The nutritional quality of aloe vera cookies was evaluated after being manufactured with all-natural, chemical-free ingredients. The primary objective was to investigate its functional properties, sensory characteristics, and quality characterization. Quality control was performed on aloe vera cookies, and the results were discussed. The process is quick and straightforward, and it comes at a reasonable cost that boosts nutrient content, but it can also be utilized as a part of a well-balanced diet. Because of its beneficial characteristics, aloe vera-based cookies could be particularly beneficial for most vulnerable groups in underdeveloped countries. The cookies are safe to eat daily as a snack food. Bangladesh J. Sci. Ind. Res. 57(2), 117-122, 2022